Semiconductor lasers : (Academic Press, 1998)
This volume presents state-of-the-art information on several important material systems and device structures employed in modern semiconductor lasers. The first two chapters discuss several III-V, II-VI, and VI-VI compound semiconductor material systems employed in diode lasers whose emission spectra cover the range from the blue to the mid-infrared. Subsequent chapters describe the elaboration of special laser structures designed for achieving narrow spectral linewidths and wavelength tunability, as well as high power emission devices. The last chapter covers the development of surface emitting diode lasers, particularly vertical cavity structures.